Negotiating positionality, reflexivity and power relations in research on men and masculinities in Ghana - Dery, Isaac (Gender, place and culture : a journal of feminist geography, 2020)
The main objective of this article is to contribute to a more critical, African-situated understanding of the complexities, emotional vulnerability, and multidimensional positionality that a male researcher is likely to face in conducting fieldwork in a native country. Drawing on my own experiences in conducting fieldwork in northwestern Ghana, the article demonstrates how a male researcher conducting interviews with his fellow countrymen could be constructed within hierarchies of masculinities; where he is simultaneously positioned as a powerless native subject and a powerful researcher. I problematise how my negotiation of fieldwork as a Ghanaian male researcher and my ideological baggage as a gender scholar could be read within the larger politics of gender and geography, as well as feminist intersectional theories. Drawing on these theories as useful analytical guides to foreground my fieldwork experiences and how I interpret my data, allow for critical understanding on the range of cultural norms, taboos, gendered subjectivities, and contested meanings which perpetuate multiple masculinities in fieldwork. My reflection from a postcolonial context contributes to growing global concerns to rethink and decolonise how we approach fieldwork.